Local Thickening and Friction Reducing to Constant Resistance in a Prefolded Energy Absorption Device - Hailiang Xu; Jiaqi Song; Dong An; Yimin Song; Xiangfeng Lv (Shock and Vibration)
The energy absorption support for impact resistance used in mining engineering is a prefolded energy absorption device. In this paper, through the quasistatic compression test and numerical simulation, the relationship between the deformation process, load-displacement curve, and plastic strain of the original prefolded energy absorbing device is studied. It is found that the concave side stiffness has an obvious effect on the first and second descending sections of the load-displacement curve, and the friction coefficient has an obvious effect on the second ascending section of that. In order to make the prefolded energy absorption device reach the state of constant resistance where the reaction load does not fluctuate or the fluctuation is small in the crushing process, the plastic strain is restrained by thickening the local area of the concave side, which effectively reduces the descending amplitude of the load-displacement curve. Whether continuoues deformation occurs is affected by the friction coefficient. Finally, a constant resistance energy absorption device is designed by thickening the concave side and reducing the friction coefficient. Compared with the original structure, the maximum bearing capacity of the constant resistance energy absorption device is basically unchanged, the average bearing capacity is increased by 29%, the total energy absorption is increased by 111%, the specific energy absorption is increased by 119%, and the load-displacement curve variance is reduced to 3% of the original structure.